2005
DOI: 10.1021/jm050595e
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of 2-Chloro-N6-substituted-4‘-thioadenosine-5‘-uronamides as Highly Potent and Selective Agonists at the Human A3 Adenosine Receptor

Abstract: We have established structure-activity relationships of novel 4'-thionucleoside analogues as the A(3) adenosine receptor (AR) agonists. Binding affinity, selectivity toward other AR subtypes, and efficacy in inhibition of adenylate cyclase were studied. From this study, 2-chloro-N(6)-methyl-4'-thioadenosine-5'-methyluronamide (36a) emerged as the most potent and selective agonist at the human A(3) AR. We have also revealed that, similar to 4'-oxoadenosine analogues, at least one hydrogen on the 5'-uronamide mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 22 publications
0
58
0
Order By: Relevance
“…[5] From this study, 2-chloro-N 6 -methyl-and 2-chloro-N 6 -(3-iodobenzyl)-4 -thioadenosine-5 -methyluronamides (K i = 0.28 ± 0.09 nM and K i = 0.38 ± 0.07 nM, respectively) were discovered as highly potent and selective agonists at the human A 3 AR. It was also found that 5 -monoalkyl amide SCHEME 1 Reagents and conditions: a) R 1 NH 2 , Et 3 N; b) 80% AcOH; c) TBSOTf, pyridine; d) NaOMe, MeOH; e) PDC, DMF; f) amines, EDC, HOBT, DIPEA, CH 2 Cl 2 ; g) TBAF, THF.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…[5] From this study, 2-chloro-N 6 -methyl-and 2-chloro-N 6 -(3-iodobenzyl)-4 -thioadenosine-5 -methyluronamides (K i = 0.28 ± 0.09 nM and K i = 0.38 ± 0.07 nM, respectively) were discovered as highly potent and selective agonists at the human A 3 AR. It was also found that 5 -monoalkyl amide SCHEME 1 Reagents and conditions: a) R 1 NH 2 , Et 3 N; b) 80% AcOH; c) TBSOTf, pyridine; d) NaOMe, MeOH; e) PDC, DMF; f) amines, EDC, HOBT, DIPEA, CH 2 Cl 2 ; g) TBAF, THF.…”
Section: Resultsmentioning
confidence: 87%
“…[5] Treatment of 4 with various alkyl-and arylalkyl amines in EtOH produced N 6 -alkyl-or arylalkylamino-4 -thioadenosine derivatives 5. Because removal of the isopropylidene group under acidic conditions at the final step resulted in deglycosylation, the isopropylidene group in 5 was changed to di-O-TBS ether 6.…”
Section: Resultsmentioning
confidence: 99%
“…The A 3 agonists IB-MECA [N 6 -(3-iodobenzyl)-5 0 -N-methylcarboxamidoadenosine; CF101] and its 2-chloro analogue Cl-IB-MECA (CF102) were the first selective agonists of the A 3 AR. Currently, more selective agonists are available, including the conformationally locked Northern (N) methanocarba derivative, MRS3558 (((1 0 R,2 0 R,3 0 S,4 0 R,5 0 S)-4-(2-chloro-6-[(3-chlorophenylmethyl)amino] purin-9-yl)-1-(methylaminocarbonyl)bicyclo[3.1.0]hexane-2,3-diol)), and the 4 0 -thio analogue of Cl-IB-MECA, LJ-529 [6,66]. MRS3558 maintains a receptor-preferred (N) conformation of the ribose-like ring.…”
Section: Modified Nucleosides As a 3 Ar Ligandsmentioning
confidence: 99%
“…IB-MECA is also entering clinical trials for chronic plaque psoriasis, keratoconjunctivitis sicca, and dry eye syndrome. [3,4,6,13,16,52,66].…”
Section: Modified Nucleosides As a 3 Ar Ligandsmentioning
confidence: 99%
“…Compound 1 is in a phase II clinical trial for hepatocellular carcinoma and is projected to enter a clinical trial for nonalcoholic steatohepatitis. 7 On the basis of the structure of 1 , its bioisosteric 4′-thio analogue 2 (thio-Cl-IB-MECA, X = S, R 1 = 3-iodobenzyl, R 2 = Cl, K i = 0.38 nM for A 3 AR) 8 was discovered as the second generation A 3 AR agonist. Compound 2 exhibited potent biological activities in models of cancer 9 and cerebral ischemia 10 with novel mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%